If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 20z + -1 + 36 = 5z + 5 Reorder the terms: -1 + 36 + 20z = 5z + 5 Combine like terms: -1 + 36 = 35 35 + 20z = 5z + 5 Reorder the terms: 35 + 20z = 5 + 5z Solving 35 + 20z = 5 + 5z Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-5z' to each side of the equation. 35 + 20z + -5z = 5 + 5z + -5z Combine like terms: 20z + -5z = 15z 35 + 15z = 5 + 5z + -5z Combine like terms: 5z + -5z = 0 35 + 15z = 5 + 0 35 + 15z = 5 Add '-35' to each side of the equation. 35 + -35 + 15z = 5 + -35 Combine like terms: 35 + -35 = 0 0 + 15z = 5 + -35 15z = 5 + -35 Combine like terms: 5 + -35 = -30 15z = -30 Divide each side by '15'. z = -2 Simplifying z = -2
| 30-x=10+0.5x | | 11=21a | | 6m=x | | 4(-2z-5)-7=10 | | 35-6= | | 100*20= | | 3r+10=2(-3r+8) | | (5x-4)3-5(4-3x)=7x+7(3x-4) | | h-13=78 | | 5p-3tq=2 | | 7x-36=3x | | 10x+13=68-x | | 9y^2-12y+1=0 | | 3x+8=2x+20 | | 7(3x+4)=9x-12-x | | 2x+3+4x+2=11 | | 13x-(25+11x)=165-2(4x+10) | | 16x^2-13x=0 | | 5x+37=179 | | 12-3(2x+9)=15 | | 3(6z-1)-4(z+2)=5(z+1) | | 4d+3=8 | | 7x+4x=12 | | -9x-1=71 | | 7x+4+=12 | | 217-5x=40x+22 | | 10-7x=127-28x | | 10-7x=127-18x | | 114-5x=2x+26 | | -8x-5=19 | | 5x^2+3x=3 | | 5y-2x=10 |